The haloes and environments of nearby galaxies (HERON) – I. Imaging, sample characteristics, and envelope diameters. Issue 2 (1st August 2019) - Rich, R Michael; Mosenkov, Aleksandr; Lee-Saunders, Henry; Koch, Andreas; Kormendy, John; Kennefick, Julia; Brosch, Noah; Sales, Laura; Bullock, James; Burkert, Andreas; Collins, Michelle; Cooper, Michael; et al.
ABSTRACT: We use a dedicated 0.7-m telescope to image the haloes of 119 galaxies in the Local Volume to μ r ∼ 28–30 mag arcsec −2 . The sample is primarily from the Two Micron All Sky Survey Large Galaxy Atlas (Jarrett et al. 2003) and extended to include nearby dwarf galaxies and more distant giant ellipticals, and spans fully the galaxy colour–magnitude diagram including the blue cloud and red sequence. We present an initial overview, including deep images of our galaxies. Our observations reproduce previously reported low surface brightness structures, including extended plumes in M 51, and a newly discovered tidally extended dwarf galaxy in NGC 7331. Low surface brightness structures, or 'envelopes', exceeding 50 kpc in diameter are found mostly in galaxies with M V < −20.5, and classic interaction signatures are infrequent. Defining a halo diameter at the surface brightness 28 mag arcsec −2, we find that halo diameter is correlated with total galaxy luminosity. Extended signatures of interaction are found throughout the galaxy colour–magnitude diagram without preference for the red or blue sequences, or the green valley. Large envelopes may be found throughout the colour–magnitude diagram with some preference for the bright end of the red sequence. Spiral and S0 galaxies have broadly similar sizes, but ellipticals extend to notably greater diameters, reaching 150 kpc. We propose that the extended envelopes of disc galaxies are dominated by an extension of the disc population rather than by a classical Population II halo.